Composite catalyst and its application and electrochemical reaction device
By designing a composite catalyst of fullerene and copper-based micro/nano structures, the problems of complex products and poor stability of existing copper-based catalysts have been solved, achieving highly efficient electrochemical catalysis for the selective reduction of CO2 to C2H4, which is suitable for electrochemical reaction devices.
Patent Information
- Application Number
- CN202310065351.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-01-13
AI Technical Summary
When existing copper-based catalysts electrochemically reduce CO2, the product composition is complex, and the Faraday efficiency of C2H4 is low and the stability is poor, making it difficult to meet the requirements for industrial applications.
A composite catalyst of fullerene and copper-based micro/nano structures was prepared by co-precipitation or co-ball milling, with a fullerene to copper mass ratio of 5-35:20. The fullerene was immobilized on the copper-based micro/nano structure to form a highly selective catalyst.
It achieves highly selective reduction of CO2 to C2H4 with a Faraday efficiency of over 30%, and the catalyst exhibits high stability, making it suitable for industrial applications.
Smart Images

Figure CN115976568B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical catalysis, and specifically relates to a composite catalyst and its application and an electrochemical reaction device, and more specifically relates to a fullerene-copper composite catalyst, and its application in electrochemical catalytic reduction of CO2, and an electrochemical reaction device containing the fullerene-copper composite catalyst. Background Art
[0002] Human activities such as fossil fuel burning, industrial manufacturing and land clearing have increased the amount of CO2 in the atmosphere. Large amounts of CO2 emissions will enhance the greenhouse effect and warm the Earth's climate. Capturing CO2 from the atmosphere and converting it into chemical raw materials and energy provides a solution to the above problems.
[0003] Electrochemical catalytic reduction of CO2 is a promising green carbon fixation technology that can use renewable electricity as energy to reduce CO2 to more valuable carbon-based products, thereby effectively achieving a closed carbon cycle and chemical energy storage.
[0004] The related technology uses copper-based catalysts to electrochemically catalytically reduce CO2. This method can obtain a mixed product containing multiple substances such as H2, CO, and C2H4. Summary of the invention
[0005] The inventors have found that the related technology uses traditional copper-based catalysts for electrochemical catalytic reduction of CO2, which can only obtain mixed products with complex components. The reaction products and reactions that may be involved are as follows:
[0006] (1)CO;CO2+2H + +2e - →CO+H2O
[0007] (2) C2H4; 2CO2+12H + +12e - →C2H4+4H2O
[0008] (3)H2; 2H + +2e - →H2.
[0009] The Faradaic efficiency of obtaining C2H4 by electrochemical reduction of CO2 using traditional copper-based catalysts is low, and the reduction products are complex and unstable, which is not conducive to subsequent further industrial applications.
[0010] The present invention provides a novel composite catalyst, which is used for the electrochemical catalytic reduction of CO2 and can reduce CO2 to C2H4 with high selectivity. The Faraday efficiency of forming C2H4 reaches more than 30%, and the proportion of C2H4 in the product is relatively high, which is conducive to the further industrial application of the product.
[0011] In a first aspect, the present application provides a composite catalyst, comprising:
[0012] Copper-based micro-nanostructures; and
[0013] Fullerene, wherein the fullerene is fixed on a copper-based micro-nanostructure;
[0014] Among them, the mass ratio of fullerene to copper element is 5-35:20.
[0015] In some embodiments, the mass ratio of fullerene to copper element is 5-30:20, such as 7-20:20, such as 8-14:20, such as 9-12:20.
[0016] In some embodiments, the mass ratio of fullerene to copper is 5-6:20, 6-7:20, 7-8:20, 8-9:20, 9-10:20, 10-11:20, 11-12:20, 12-13:20, 13-14:20, 14-15:20, 15-16:20, 16-17:20, 17-18:20, 18-19:20, 19- 20:20, 20-21:20, 21-22:20, 22-23:20, 23-24:20, 24-25:20, 25-26:20, 26-27:20, 27-28:20, 28-29:20, 29-30:20, 30-31:20, 31-32:20, 32-33:20, 33-34:20 or 34-35:20.
[0017] In some embodiments, the composite catalyst includes 5 to 90 wt% of copper-based micro-nano structures, optionally 5 to 70 wt%, optionally 5 to 60 wt%, optionally 5 to 50 wt%, optionally 5 to 40 wt%, optionally 5 to 30 wt%, optionally 5 to 20 wt%, optionally 5 to 15 wt%, and optionally 5 to 10 wt%.
[0018] In some embodiments, the copper-based micro-nanostructure includes one or more of the following: a copper-based micron structure, a copper-based nanostructure.
[0019] In some embodiments, the copper-based micro-nanostructure comprises Cu + .
[0020] In some embodiments, the copper-based micro-nanostructure includes Cu 0 .
[0021] In some embodiments, the copper-based micro-nanostructure includes Cu 2+ .
[0022] In some embodiments, the copper-based micro-nanostructure comprises the following components: Cu 0 and Cu + .
[0023] In some embodiments, the copper-based micro-nanostructure comprises the following components: Cu 0 , Cu + and Cu 2+ .
[0024] In some embodiments, the Cu element Auger electron spectrum of the composite catalyst corresponds to Cu + and Cu 0 The peak area ratio of the characteristic peaks is 50:50 or more, for example 60-99:1-40, for example 70-99:1-30, for example 60-95:5-40, for example 70-95:5-30, for example 60-90:10-40, for example 70-90:10-30, for example 60-80:20-40, for example 70-80:20-30 (for example 74.5:25.5).
[0025] In some embodiments, the Cu element Auger electron spectrum of the composite catalyst corresponds to Cu + The characteristic peak of is in the range of 913-915 eV, such as in the range of 914.5-915.5 eV, such as around 914.0 eV.
[0026] In some embodiments, the Cu element Auger electron spectrum of the composite catalyst corresponds to Cu + The characteristic peak of is in the range of 916-919 eV, such as in the range of 917-918 eV, such as around 917.5 eV.
[0027] In some embodiments, the deconvolution method is used to obtain the Cu element Auger electron spectrum corresponding to Cu + and Cu 0 The characteristic peak of Cu + and Cu 0 The characteristic peak has, for example, a symmetrical peak shape, such as a Gaussian peak or a Lorentz peak.
[0028] In some embodiments, the copper-based micro-nanostructures contain cuprous (Cu + )'s mass content may be selected from 1 to 100%, may be selected from 10 to 95%, may be further selected from 20 to 90%, may be selected from 30 to 80 wt%, may be selected from 40 to 75 wt%, may be selected from 50 to 70 wt%, may be selected from 60 to 65 wt%.
[0029] In some embodiments, the material of the copper-based micro-nanostructure includes one or more of the following: cuprous oxide, cuprous sulfide, cuprous chloride, cuprous sulfate, cuprous nitrate, and cuprous acetate.
[0030] In some embodiments, the material of the copper-based micro-nanostructure further comprises one or more of the following: copper oxide, copper sulfide, copper chloride, copper sulfate, copper nitrate, copper acetate, and copper phyllosilicate.
[0031] In some embodiments, the material of the copper-based micro-nanostructure includes one or more of the following: cupric oxide, cuprous oxide, copper sulfide, cuprous sulfide, cupric chloride, cuprous chloride, cupric sulfate, cuprous sulfate, cupric nitrate, cuprous nitrate, cupric acetate, cuprous acetate, and copper phyllosilicate.
[0032] In some embodiments, the copper-based micro-nanostructure contains cuprous oxide (Cu2O).
[0033] In some embodiments, the copper-based micro-nanostructure further contains one or more of the following components: copper (Cu), copper oxide (CuO), and copper phyllosilicate.
[0034] In some embodiments, the copper-based micro-nanostructure contains one or more of the following components: copper (Cu), copper oxide (CuO), cuprous oxide (Cu2O), and copper phyllosilicate.
[0035] In the present invention, the copper-based micro-nano structure includes copper nanoparticles, and the particle size of the copper nanoparticles can be selected to be 0.5-10 nm, 0.5-6 nm, 1-5 nm, and further 1-4 nm.
[0036] In some embodiments, the copper-based micro-nanostructure has a 10 m 2 / g or more. Optionally, the copper-based micro-nanostructure has a surface area of 20m 2 / g or more. Optionally, the copper-based micro-nanostructure has a surface area of 30m 2 / g or more. Optionally, the copper-based micro-nanostructure has a surface area of 30-40 m 2 Optionally, the copper-based micro-nanostructure has a surface area of 30-50 m 2 / g of surface area.
[0037] In some embodiments, fullerenes are immobilized on copper-based micro-nanostructures.
[0038] In some embodiments, the fullerene is fixed to the copper-based micro-nanostructure via covalent bonds.
[0039] In some embodiments, the fullerene is fixed to the copper-based micro-nanostructure via a C-Cu covalent bond.
[0040] In some embodiments, the composite catalyst has 10m 2 / g or more, for example, a BET specific surface area of 100 m 2 / g or more, for example, 200 m 2 / g or more, for example, 300 m 2 / g or more, for example, 300-400m 2 / g BET specific surface area, for example, 300-500m 2 / g BET specific surface area.
[0041] In some embodiments, the composite catalyst further comprises a carrier, and the copper-based micro-nanostructure is fixed on the carrier.
[0042] In some embodiments, the carrier comprises micron-sized particles and / or nano-sized particles.
[0043] In some embodiments, the material of the carrier includes inorganic substances, such as inorganic oxides or ceramics. The material of the carrier includes, for example, one or more of the following: SiO2, Al2O3, TiO2, silicate, diatomaceous earth, zeolite, molecular sieve.
[0044] In some embodiments, the mass ratio of fullerene, copper element and carrier in the composite catalyst is x:y:(100-xy).
[0045] In some embodiments, x has a value of 5-30:20.
[0046] In some embodiments, x has a value of 7-20:20.
[0047] In some embodiments, x has a value of 8-14:20.
[0048] In some embodiments, x has a value of 9-12:20.
[0049] In some embodiments, y has a value of 10-30.
[0050] In some embodiments, y has a value of 15-25.
[0051] In some embodiments, y has a value of 18-22.
[0052] In some embodiments, y has a value of 20.
[0053] In some embodiments, x is 5-6, 6-7, 7-8, 8-9, 9-10, 10-11, 11-12, 12-13, 13-14, 14-15, 15-16, 16-17, 17-18, 18-19, 19-20, 20-21, 21-22, 22-23, 23-24, 24-25, 25-26, 26-27, 27-28, 28-29, 29-30, 30-31, 31-32, 32-33, 33-34, or 34-35.
[0054] In some embodiments, y has a value of 10-11, 11-12, 12-13, 13-14, 14-15, 15-16, 16-17, 17-18, 18-19, 19-20, 20-21, 21-22, 22-23, 23-24, 24-25, 25-26, 26-27, 27-28, 28-29, 29-30, 30-31, 31-32, 32-33, 33-34, or 34-35. 20-21, 21-22, 22-23, 23-24, 24-25, 25-26, 26-27, 27-28, 28-29, or 29-30.
[0055] In some embodiments, the support includes an inorganic support. Optionally, the inorganic support is preferably one or more of silicon dioxide, zinc oxide, aluminum oxide, zirconium oxide, cerium oxide, magnesium oxide, carbon nanotubes, activated carbon, graphene, and boron nitride.
[0056] In some embodiments, the inorganic carrier serves as a skeleton of fullerene and copper-based micro-nanostructures, and can support fullerene and nano-copper so that the two components are evenly dispersed, while increasing the physical strength and electrochemical activity of the material.
[0057] In some embodiments, the particle size of the inorganic carrier is 10 to 500 nm, optionally 50 to 400 nm, optionally 100 to 350 nm, and optionally 200 to 350 nm.
[0058] In some embodiments, the chemical composition of the fullerene may be C 2n 、M@C 2n 、M2@C 2n 、MA@C 2n 、M3N@C 2n 、M2C2@C 2n (endohedral bimetallic carbide cluster fullerene), M2S@C 2n 、M2O@C 2n 、M x A 3-x @C 2n , C 2nH 2y , C 2n Cl 2y One or more of; in the present invention, @ represents doping; the M and A are each independently one of Sc, Y and lanthanide metals, and M and A are different; 25≤n≤60, optionally 30≤n≤50; 0≤x≤3, optionally 1≤x≤2; 0≤y≤20, optionally 5≤y≤10.
[0059] In some embodiments, the chemical composition of the fullerene is C 60 , C 70 , C 76 , C 84 、Gd@C 82 , C 50 Cl 10 , C 60 Cl 10 Sc2C2@C 80 Sc3N@C 82 Sc2S@C 82 Sc2O@C 82 , C 60 H 10 , C 64 One or more of H4.
[0060] In some embodiments, the fullerene comprises one or more of the following: 60 , C 70 .
[0061] In some embodiments, the fullerene includes one or more of the following: hollow fullerene, endohedral fullerene, heterocyclic fullerene, exofullerene.
[0062] In some embodiments, a heterocyclic fullerene is, for example, a fullerene in which one or more carbon atoms are replaced by a non-carbon atom (e.g., one or more of a boron, nitrogen, oxygen, arsenic, germanium, phosphorus, silicon, iron, copper, nickel, rhodium, or iridium atom).
[0063] In some embodiments, the exofullerene is bound by one or more H, Cl or C 1-20 Alkyl (e.g. C 1-6 Fullerene modified with alkyl) cage. 1-20 "Alkyl" refers to, for example, a linear, cyclic or branched hydrocarbon group containing 1 to 20 carbon atoms, such as methyl, ethyl, propyl, isopropyl, cyclopropyl, butyl, tert-butyl, isobutyl, cyclobutyl, pentyl, cyclopentyl, hexyl, cyclohexyl, hexadecyl, heptadecyl, octadecyl, nonadecyl. "C 1-6 The term "alkyl" refers to, for example, a linear, cyclic or branched hydrocarbon group containing 1 to 6 carbon atoms, such as methyl, ethyl, propyl, isopropyl, pentyl, cyclopentyl, hexyl and cyclohexyl.
[0064] In some embodiments, "endohedral fullerene" refers to a compound in which any atom, ion, or atom cluster (eg, metal atom) is enclosed within the carbon cage structure of the fullerene.
[0065] In some embodiments, the particle size of a fullerene molecule is 0.5 to 1.0 nm, and optionally 0.6 to 0.9 nm.
[0066] In a second aspect, the present application provides use of any of the composite catalysts described above for electrochemical catalytic reduction of CO2 to obtain C2H4.
[0067] In some embodiments, the Faradaic efficiency of electrochemical catalytic reduction of CO2 to obtain C2H4 is 30% or more, such as 40% or more, such as 50% or more, such as 60% or more.
[0068] In a third aspect, the present application provides a method for electrochemical catalytic reduction of CO2 to obtain C2H4, comprising: contacting CO2 with an electrode containing a catalyst; the catalyst is any of the composite catalysts described above.
[0069] In some embodiments, CO2 is contacted with an electrode containing a catalyst in an electrolyte environment.
[0070] In some embodiments, the electrolyte can be selected from one or more of sodium chloride solution, potassium chloride solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium hydroxide solution, potassium hydroxide solution, and tetrabutylammonium hexafluorophosphonate solution.
[0071] In some embodiments, a gas diffusion electrode is used to contact CO2 with an electrode containing a catalyst. A gas diffusion electrode is, for example, an electrode comprising a hydrophobic gas diffusion layer and a reaction layer and a suitable electrode substrate. A gas diffusion electrode is, for example, any of the gas diffusion electrodes described in the following documents: Rabiee H, Ge L, Zhang X, et al. Gasdiffusion electrodes (GDEs) for electrochemical reduction of carbon dioxide, carbon monoxide, and dinitrogen to value-added products: a review [J]. Energy & Environmental Science, 2021, 14 (4): 1959-2008. The entire document is cited here.
[0072] In some embodiments, the Faradaic efficiency for obtaining C2H4 is 30% or more, such as 40% or more, such as 50% or more, such as 60% or more.
[0073] In some embodiments, the method for electrochemical catalytic reduction of CO2 further comprises the step of applying a voltage of -0.8 V vs. RHE to -1.3 V vs. RHE to the electrode.
[0074] In some embodiments, in the method for electrochemical catalytic reduction of CO2, the following chemical reaction occurs:
[0075] CO2+2H + +2e - →CO + H2O; and
[0076] 2CO2+12H + +12e - →C2H4+4H2O.
[0077] In some embodiments, based on the use of the novel composite catalyst of the present application, those skilled in the art can realize the technical solution of the present invention by using the electrochemical catalytic reduction technology commonly used in the art to realize CO2. The commonly used electrochemical catalytic reduction in the art can refer to the following document: Electrochemical reduction of carbon dioxide: fundamentals and technologies [M]. CRC press, 2016. The entire text of the document is hereby cited.
[0078] In a fourth aspect, the present invention provides a method for preparing the composite catalyst, comprising the following steps:
[0079] Providing a precursor, wherein the precursor contains a fullerene-copper co-precipitation product and / or a fullerene-copper co-milling product;
[0080] calcining the precursor to obtain a calcined product;
[0081] The calcined product is subjected to reduction treatment to obtain the composite catalyst.
[0082] In some embodiments, the method for preparing the fullerene-copper co-precipitation product includes: heating and mixing fullerene, water, a soluble copper salt and a precipitant to obtain the fullerene-copper co-precipitation product.
[0083] In some embodiments, the method for preparing the fullerene-copper co-precipitation product comprises: heating and mixing fullerene, water, a soluble copper salt, a carrier and a precipitant to obtain the fullerene-copper co-precipitation product.
[0084] In some embodiments, the fullerene is preferably added in the form of a fullerene dispersion. The solvent of the fullerene dispersion can be selected from water, methanol, ethanol, benzene, toluene, xylene, carbon disulfide, and can be selected from water, ethanol, toluene, and xylene. In some embodiments, the method for preparing the fullerene dispersion preferably includes the following steps:
[0085] In some embodiments, fullerenes are ultrasonically mixed with water to obtain an aqueous dispersion of fullerenes.
[0086] In some embodiments, the power of ultrasonic mixing can be 35-45 W, or 40 W; the time can be 25-45 min, or 30 min. In some embodiments, the mass concentration of the fullerene aqueous dispersion can be 0.01-0.05 g / mL.
[0087] In some embodiments, the soluble copper salt may be selected from one or more of copper oxide, cuprous oxide, copper sulfide, cuprous sulfide, cupric chloride, cuprous chloride, cupric sulfate, cuprous sulfate, cupric nitrate, cuprous nitrate, cupric acetate, and cuprous acetate. In some embodiments, the soluble copper salt is preferably added in the form of a soluble copper salt aqueous solution, and the molar concentration of the soluble copper salt may be selected from 0.05 to 0.6 mol / L, and may be selected from 0.1 to 0.4 mol / L.
[0088] In some embodiments, the precipitant may be one or more of urea, ammonia water, sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide and sodium borohydride, and may be one of ammonia water, urea, sodium carbonate and potassium carbonate. Sodium carbonate is the most preferred. In some embodiments, the mass concentration of ammonia water may be 0.05 to 3.0 mol / L, and may be 0.2 to 2.5 mol / L.
[0089] In some embodiments, the mass ratio of the precipitant to the copper salt may be 1 to 5:1, or 2 to 4:1. In some embodiments, the precipitant is preferably added in the form of an aqueous solution of the precipitant, and the molar concentration of the aqueous solution of the precipitant may be 0.5 to 2.0 mol / L, or 1.0 to 1.5 mol / L.
[0090] In some embodiments, the temperature of the heating and mixing can be selected from 30 to 120° C., can be selected from 50 to 110° C., and most preferably from 60 to 90° C.; the time can be selected from 1 to 72 hours, can be selected from 2 to 48 hours, and most preferably from 2 to 24 hours. In some embodiments, the heating and mixing is preferably carried out under stirring, and the stirring speed can be selected from 200 to 900 r / min, and can be selected from 400 to 800 r / min.
[0091] In some embodiments, after heating and mixing, the present invention optionally filters, washes and dries the obtained mixed solution in sequence to obtain a fullerene-copper coprecipitation product. In some embodiments, the copper coprecipitation product can be selected from copper hydroxide, copper ammonia complex or copper carbonate. The present invention has no special requirements for the filtering method, and the filtering method familiar to those skilled in the art can be used. In some embodiments, the washing temperature can be selected from room temperature, and the washing detergent used for washing can be selected from water, anhydrous ethanol and acetone, and can be selected from deionized water and anhydrous ethanol. In the present invention, the washing process can be selected as: washing with water 2 to 3 times, and then washing with anhydrous ethanol once. The present invention does not have any special restrictions on the amount of water and anhydrous ethanol used, and it can ensure that the pH value of the final washing liquid is neutral.
[0092] In some embodiments, the drying temperature may be 80 to 120° C., or 90 to 100° C.; the drying time may be 6 to 24 hours, or 12 to 18 hours.
[0093] In some embodiments, the method for preparing the fullerene-copper co-ball milling product includes: ball milling and mixing fullerene and a soluble copper salt to obtain a ball milling product.
[0094] In some embodiments, the method for preparing the fullerene-copper co-ball milling product comprises: ball milling the fullerene, the carrier and the soluble copper salt to obtain a ball milling product.
[0095] In some embodiments, the soluble copper salt may be selected from one or more of copper nitrate, cuprous nitrate, copper sulfate, cuprous sulfate, copper sulfide, cuprous sulfide, copper acetate, cuprous acetate, cupric chloride and cuprous chloride.
[0096] In some embodiments, the ball milling instrument can be a planetary ball mill. The present invention has no special requirements for the equipment used in the planetary ball mill, and the equipment familiar to those skilled in the art can be used. The material of the ball mill and the ball milling beads can be agate, stainless steel, zirconium oxide, and agate. In some embodiments, the frequency of ball milling can be 10 to 60 Hz, 20 to 50 Hz; the ball milling time can be 1 to 24 hours, 8 to 16 hours, and 12 hours.
[0097] In some embodiments, the calcination atmosphere may be air.
[0098] In some embodiments, the calcination temperature may be 250-500°C, 250-350°C, and the holding time may be 1-12 hours, 2-8 hours, or 3-6 hours. The present invention has no special requirements for the equipment used for calcination, and equipment familiar to those skilled in the art may be used. In the embodiments of the present invention, the calcination equipment is specifically a muffle furnace.
[0099] In some embodiments, the reduction reduces the divalent copper oxide in the calcined material to zero-valent copper and / or monovalent copper.
[0100] In some embodiments, the reducing comprises electrochemically reducing at a potential of -0.8 V vs RHE to -1.3 V vs RHE.
[0101] In some embodiments, the electrolyte for electrochemical reduction can be selected from one or more of sodium chloride solution, potassium chloride solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium hydroxide solution, potassium hydroxide solution, and tetrabutylammonium hexafluorophosphonate solution.
[0102] In some embodiments, the reduction includes heat treatment under a hydrogen atmosphere, and the flow rate of the hydrogen can be 10 to 200 mL / min, 30 to 100 mL / min, and most preferably 40 to 50 mL / min. Optionally, the temperature of the reduction can be 250 to 350°C, 300 to 320°C, and the holding time can be 1 to 12 hours, or 5 to 10 hours.
[0103] In a fifth aspect, the present application provides an electrochemical reaction device, comprising:
[0104] An electrode containing a catalyst, wherein the catalyst is any of the composite catalysts described above; and
[0105] A distributor is configured to distribute CO2 to the electrode containing the catalyst.
[0106] In some embodiments, the electrochemical reaction device is used for electrochemical catalytic reduction of CO2 to obtain C2H4.
[0107] In some embodiments, the distributor is a baffle.
[0108] Terminology
[0109] As used herein, the term "catalyst" refers to a material that initiates and / or promotes a chemical reaction, such as a material that increases the rate of a reaction.
[0110] As used herein, the term "electrochemical catalysis" refers to initiating and / or promoting an electrochemical reaction, such as increasing the rate of an electrochemical reaction.
[0111] The term "electrochemical reduction" refers to the use of electrical energy to convert a chemical species into a more reduced chemical species.
[0112] The term "cathode" refers to the electrode at which reduction occurs during application of an electrical potential.
[0113] The term "fullerene" as used herein refers to a particle or molecule having a cage as a core structure. The cage structure preferably has an aspect ratio of 10 or less. Examples of fullerenes include carbon cage molecules comprising a three-dimensional skeleton including a plurality of carbon atoms, the carbon cage molecules forming a closed shell, and the shape of the carbon cage molecules may be spherical or hemispherical. Fullerene molecules may be named C 2n , where n is an integer corresponding to the number of carbon atoms included in the carbon skeleton of the fullerene molecule. Examples of fullerene molecules include C 2n , where 2n is in the range of 50 to 250, for example C 60 , C 70 , C 72 , C 74 , C 76 , C 78 , C 80 , C 82 and C 84 Other examples of fullerene molecules include tubular or cylindrical carbon molecules, such as single-walled carbon nanotubes and multi-walled carbon nanotubes. An example of a fullerene is Buckminsterfullerene or Buckyball, which is similar to a soccer ball and includes pentagonal and hexagonal rings. The term fullerene as used herein may be understood in a broad sense, i.e., including all-carbon fullerene and any derivatives thereof. Optionally, the fullerene is, for example, any of the fullerenes described in the following document: Deng Shunliu, Tan Yuanzhi, Xie Suyuan, et al. Research Progress on New Structures of Fullerenes [J]. Journal of Xiamen University: Natural Science Edition, 2011, 50(2):12. The entire document is hereby cited.
[0114] The term "particle" or "particle" is a general term that can include particles of any size. A particle can include one or more types of structures (e.g., crystal structure, defect concentration, etc.) and one or more types of atoms. A particle can be of any shape, including but not limited to spherical, spherical, dumbbell-shaped, cylindrical, elongated cylindrical, quadrangular prism-shaped, disc-shaped, linear, irregular shape, dense shape (e.g., with few voids), porous shape (e.g., with many voids), etc.
[0115] The term "micro-nano" refers to micrometers and / or nanometers. The term "micrometer" refers to 1-1000 μm, such as 1-10 μm, 10-100 μm or 100-1000 μm. The term "nano" refers to 1-10 nm, 10-100 nm or 100-1000 nm (excluding 1000 nm itself).
[0116] The term "micro-nano structure" refers to a structure having micro-nano dimensions in at least one dimension. For example, a structure having micro-nano dimensions in one dimension. For example, a structure having micro-nano dimensions in two mutually perpendicular dimensions. For example, a structure having micro-nano dimensions in three mutually perpendicular dimensions.
[0117] The term "guide plate" is also commonly referred to as a polar plate or a bipolar plate, which can achieve two basic functions, namely (1) due to the presence of mutually interpenetrating radial grooves and circumferential grooves in the flow field area of the guide plate, the fluid (such as the reactants and products of the electrochemical reaction device) can enter the guide plate from the through hole and flow along these grooves, and finally enter another through hole to flow out of the electrochemical reaction cell, that is, it serves as a flow channel for the fluid (such as the reactants and products of the electrochemical reaction cell); (2) after the guide plate provides a fluid channel, due to the presence of the circumferential ridge, the circumferential ridge contacts the diffusion layer of the electrochemical reaction device, thereby achieving electrical contact between the guide plate (i.e., the polar plate) and the diffusion layer.
[0118] For the purpose of this specification and the appended claims, unless otherwise stated, all numbers indicating quantity, percentage or ratio, as well as other numerical values used in the specification and claims, should be understood to be modified by the term "about" in all cases. The use of the term "about" applies to all numerical values, whether or not explicitly stated. The term generally refers to a numerical range that a person of ordinary skill in the art would consider to be a reasonable deviation amount (i.e., having an equivalent function or result) to the listed numerical values. For example, the term can be interpreted as including deviations of ±10%, optionally ±5%, optionally ±1%, optionally ±0.5% and optionally ±0.1% of a given numerical value, as long as such deviations do not change the end function or result of the value. Therefore, unless otherwise stated, the numerical parameters listed in this specification and the appended claims are approximate values, which may vary according to the desired performance sought to be obtained by the present invention.
[0119] As used in this specification and the appended claims, the singular forms "a", "an", and "the" include plural references unless expressly and unequivocally limited to one reference. The term "include" and its grammatical variants as used herein are non-restrictive, such that enumerating items in a list does not exclude other similar items that can be replaced or added to the listed items. For example, as used in this specification and the appended claims, the term "include" (as well as forms, derivatives, or variations thereof, such as containing, including, having) is an open description, i.e., additional elements or steps are not excluded. Therefore, these terms are intended to cover not only the listed elements or steps, but also other elements or steps that are not explicitly listed.
[0120] In some embodiments, "comprising" means that the content is greater than zero, for example, the content is 0.1-1%, 1-10%, 1-10%, 10-20%, 20-30%, 30-40%, 40-50%, 50-60%, 60-70%, 70-80%, 80-90%, 90%-99%, 99-100% or 100%.
[0121] Additionally, as used herein, the term "a" may mean "one", but it may also be consistent with the meaning of "one or more" or "at least one".
[0122] Beneficial Effects
[0123] The present disclosure has one or more of the following beneficial effects:
[0124] (1) The composite catalyst disclosed in the present invention can reduce CO2 to C2H4 with high selectivity, and the Faradaic efficiency of C2H4 accounts for more than 30%.
[0125] (2) The composite catalyst disclosed in the present invention has high stability.
[0126] (3) The composite catalyst disclosed in the present invention has high catalytic efficiency.
[0127] (4) In the composite catalyst disclosed in the present invention, fullerene, as a unique electron reservoir for receiving or providing electrons, can regulate the valence state of copper in close contact with it by absorbing a single electron from the circuit or providing a single electron to divalent copper, so that Cu + Cu 0 The transition of Cu + Completely converted to Cu 0 , thus stabilizing Cu + The effect of valence. BRIEF DESCRIPTION OF THE DRAWINGS
[0128] Figure 1 (A) shows a macroscopic photograph of the Cu / SiO2 composite catalyst.
[0129] Figure 1 (B) shows an embodiment of C 60 -Macroscopic photograph of Cu / SiO2 composite catalyst.
[0130] Figure 1 (C) shows an embodiment of C 60 -XRD spectra of the Cu / SiO2 composite catalyst before and after use, and XRD spectra of a comparative example of the Cu / SiO2 composite catalyst before and after use.
[0131] Figure 1 (D) shows an embodiment of C 60-High-resolution TEM image of Cu / SiO2 composite catalyst.
[0132] Figure 2 (A) shows an embodiment of C 60 -High-resolution TEM image of Cu / SiO2 composite catalyst.
[0133] Figure 2 (B) is an EDX scan, showing C 60 -Distribution of Cu element on SiO2 carrier in Cu / SiO2 composite catalyst; the distribution of Cu element is represented by cyan dots, and the white frame corresponds to the SiO2 carrier.
[0134] Figure 2 (C) is an EDX scan, showing C 60 -Distribution of C element on SiO2 support in Cu / SiO2 composite catalyst; the distribution of C element is represented by red dots, and the white frame corresponds to the SiO2 support.
[0135] Figure 3 For a typical 10% C 60 -Auger electron spectra of Cu element in 20%Cu / 70%SiO2 and Cu / SiO2 composite catalysts.
[0136] Figure 4 Schematic diagram of an electrochemical reaction device. DETAILED DESCRIPTION
[0137] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0138] Example 1
[0139] The composite catalyst prepared below has the general formula
[0140] xC 2n -yCu / zSiO2
[0141] x, y, z represent C 2n , the weight percentage of Cu and SiO2, x+y+z=100%.
[0142] C 2n Represents fullerene, n=25-60.
[0143] Below is xC 60 -yCu / zSiO2 (x=10%, y=20%, z=70%) is taken as an example, and its preparation method is as follows: 0.85g C 60 Ultrasonic stirring in 150 ml of deionized water, C 60 Dispersed solution. 6.5g of copper nitrate trihydrate, 15g of silicon dioxide dispersion ( AS-40, a colloidal silica aqueous dispersion having a solid content of 40%) was added to the above C 60 In the dispersion, after mixing and ultrasonic stirring, a mixed solution is obtained, and then 150mL of 1.5mol / L urea aqueous solution is added to the above solution and mixed evenly. The above operations are all carried out at room temperature, the ultrasonic power is 30W, the stirring speed of each step is 600r / min, and the ultrasonic stirring time is 30min. The above mixed solution is transferred to the reactor, stirred at 600r / min for 16h at 92℃ and aged for 3h. After the reaction of the above mixed solution is completed and cooled to room temperature, the coprecipitated product is obtained by suction filtration, and the coprecipitated product is washed with deionized water 2 to 3 times, and then washed twice with anhydrous ethanol. The obtained suction filtration product is dried at 80℃ for 24h, the dried product is ground into powder and continued to be transferred to the muffle furnace and heated to 350℃ at 2℃ / min and calcined for 8h. The calcined product was made into a slurry and sprayed on the surface of carbon paper. It was used as the cathode in an electrochemical reaction device and reduced in a 2M potassium bicarbonate aqueous solution at a voltage of -0.8V (vs. RHE) for 30 minutes. 60 -Carbon electrode with 20%Cu / 70%SiO2 composite catalyst.
[0144] Embodiment 2-9
[0145] The difference between Example 2-9 and Example 1 is that by adjusting the amount of fullerene, copper nitrate trihydrate and SiO2 dispersion added in the raw material, a composite catalyst xC having various x, y and z values is obtained. 2n -yCu / zSiO2.
[0146] The amounts of raw materials added, the general formula of the products and the x:y values in Examples 1-9 are shown in Table 1.
[0147] Table 1
[0148]
[0149] Example 10
[0150] The C in Example 1 60 The mass ratio of C is 1:1. 60 With C 70The mixture has a mass of 0.85 g, and the other steps are the same as those in Example 1 to obtain a composite catalyst having the general formula of 5% C 60 -5%C 70 -20%Cu / 70%SiO2.
[0151] Embodiment 11
[0152] The fullerene C in Example 1 60 The amount of fullerene mixed extract (fullerene mixed extract is C 60 -C 120 The fullerene composition is 50wt% C 60 , 15wt% C 70 , the balance is fullerenes of other carbon numbers), and the other steps are the same as in Example 1 to obtain a 10% C60 (TP) -20% Cu / SiO2 functional material.
[0153] Example 12
[0154] 0.85 g C 60 Ultrasonic stirring in 150 ml of deionized water, C 60 Dispersed solution. Add 6.5g of copper nitrate trihydrate and 6g of alumina (Acmec, α-Al2O3, particle size 200nm) to the above fullerene dispersion, mix and ultrasonically stir to obtain a mixed solution, then add 150mL of 1.5mol / L urea aqueous solution to the above solution and mix evenly. The above operations are all carried out at room temperature, the ultrasonic power is 30W, the stirring speed of each step is 600r / min, and the ultrasonic stirring time is 30min. The above mixed solution is transferred to a reactor, stirred at 600r / min for 16h at 92℃ and aged for 3h. After the reaction of the above mixed solution is completed and cooled to room temperature, the coprecipitated product is obtained by suction filtration, and the coprecipitated product is washed with deionized water 2 to 3 times, and then washed twice with anhydrous ethanol. The filtered product was dried at 80°C for 24 h, ground into powder and transferred to a muffle furnace, heated to 350°C at 2°C / min and calcined for 8 h to obtain a 10% C60-20% Cu / Al2O3 functional material.
[0155] Example 13
[0156] 0.85 g C 60 , 6.5 g of copper nitrate trihydrate and 6 g of nano silicon dioxide powder (Aladdin, SiO2, particle size 7-40 nm) were put into a ball mill and milled for 12 h to obtain a powder product, which was transferred to a muffle furnace and heated to 350 ° C at 2 ° C / min and calcined for 8 h to obtain 10% C 60 -20%Cu / 70%SiO2 ball milled functional materials.
[0157] Comparative Example 1
[0158] The C in Example 1 60 The addition amount was changed to zero, the amount of silicon dioxide dispersion was changed to 17.2 g, and the other steps were the same as in Example 1 to obtain a composite catalyst with the general formula of 20% Cu / 80% SiO2.
[0159] Comparative Example 2
[0160] The fullerene C in Example 1 60 The amount of silica sol was changed to 3.2, the amount of silica sol was changed to 8.2g, and the other steps were the same as in Example 1 to obtain a composite catalyst with the general formula of 40%C 60 -20%Cu / 40%SiO2.
[0161] Comparative Example 3
[0162] The fullerene C in Example 1 60 The mass of silica was changed to 2.6 g, the mass of silicon dioxide was changed to 17.3 g, and the other steps were the same as in Example 1 to obtain 3% C 60 -20%Cu / 77%SiO2 functional material.
[0163] Analysis and testing
[0164] (1) Morphology and structure analysis
[0165] Figure 1 (A) shows a macroscopic photograph of a Cu / SiO2 composite catalyst of a comparative example, wherein a light blue-green powder is shown.
[0166] Figure 1 (B) shows an example of 10% C 60 - Macroscopic photo of 20%Cu / 70%SiO2 composite catalyst. The photo shows black powder.
[0167] Figure 1 (C) shows an example of 10% C 60 -20%Cu / 70%SiO2 composite catalyst XRD spectrum with C 60 The diffraction peaks of SiO2 (10.8°, 17.7°, 20.8°), SiO2 (22°), Cu2O (36.6°), and copper phyllosilicate (31.2°, 56.6°, 62.6°, 71.4°) are clearly visible, and the phase signal of CuO is weak, which proves that Cu is highly dispersed on the carrier.
[0168] Figure 1 (C) also shows an example of an embodiment after use 10% C 60-20%Cu / 70%SiO2 composite catalyst (used as a catalyst in the electrochemical reaction device for electrochemical catalytic reduction of CO2 for 30min) XRD spectrum, XRD diffraction peak signal has no obvious change. This shows that 10%C 60 -20%Cu / 70%SiO2 composite catalyst has improved structural stability,
[0169] Figure 1 (C) also shows an XRD spectrum of the Cu / SiO2 composite catalyst of Comparative Example 1, which has a diffraction peak (22°) of SiO2.
[0170] Figure 1 (C) also shows that a Cu / SiO2 composite catalyst of Comparative Example 1 (used as a catalyst in an electrochemical reaction device to electrochemically reduce CO2 for 30 min) has obvious Cu diffraction peaks (46.8°, 55.6°) after use. This indicates that the structural stability of the Cu / SiO2 composite catalyst is poor.
[0171] Figure 1 (D) shows an example of 10% C 60 -High-resolution TEM photo of 20%Cu / 70%SiO2 composite catalyst. The figure shows Cu nanoparticles dispersed in the SiO2 carrier. The size of multiple Cu nanoparticles in the high-resolution TEM photo was measured, and the average particle size of the Cu nanoparticles was calculated to be 3nm.
[0172] Figure 2 (A) shows an example of 10% C 60 -High-resolution TEM image of 20%Cu / 70%SiO2 composite catalyst.
[0173] right Figure 2 (A) was scanned by EDX to obtain Figure 2 EDX scans shown in (B) and (C). Figure 2 (B) shows the distribution of Cu elements on the SiO2 carrier obtained from the EDX surface scan image; the distribution of Cu elements is represented by cyan dots, and the white frame corresponds to the SiO2 carrier. Figure 2 (C) shows the distribution of C elements on the SiO2 carrier obtained from the EDX surface scan; the distribution of C elements is represented by red dots, and the white frame corresponds to the SiO2 carrier.
[0174] Figure 3 For a typical use after 10% C 60-20%Cu / 70%SiO2 composite catalyst and the Cu / SiO2 composite catalyst after use. The Cu Auger electron spectrum of the catalyst was obtained by ThermoScientific NEXSA (ThermoFisher). α Source (Mono Al K α , hv=1486.6eV). The binding energy was calibrated using the C1s peak at 284.8eV as a reference, and the experimental error was within 0.2eV.
[0175] like Figure 3 As shown, 10% C 60 The Auger electron spectrum of Cu element in the 20%Cu / 70%SiO2 composite catalyst is deconvoluted into two overlapping peaks near 914.0eV and 917.5eV, corresponding to Cu + and Cu 0 , corresponding to Cu + The peak area accounts for 74.5%, corresponding to Cu 0 The peak area accounts for 25.5%. The Auger electron spectrum of Cu element in Cu / SiO2 composite catalyst is deconvoluted into two overlapping peaks near 914.0eV and 917.5eV, which are respectively attributed to Cu + and Cu 0 , corresponding to Cu + The peak area accounts for 45.1%, corresponding to Cu 0 The peak area of 10%C accounts for 54.9%. 60 -20%Cu / 70%SiO2 composite catalyst has higher Cu + The proportion of higher Cu + The ratio is favorable for the electrochemical catalytic reduction of CO2 to produce C2H4.
[0176] (2) Analysis of physical and chemical parameters
[0177] For Example 1, 10% C 60 -20%Cu-70%SiO2 was analyzed for the following physical and chemical parameters, including:
[0178] (1) Determine the copper content in the catalyst using an inductively coupled plasma optical emission spectrometer (ICP-OES);
[0179] (2) Determination of C in the catalyst by thermogravimetric analysis (TGA) 60 content;
[0180] (3) The specific surface area of the composite catalyst was determined using the Brunauer-Emmett-Teller method.
[0181] (4) Determination of Cu surface area by nitrous oxide titration.
[0182] 2Cu(s)+N2O→Cu2O(s)+N2
[0183] where Cu(s) is a surface copper atom.
[0184] The test results are shown in the following table:
[0185] Table 2
[0186]
[0187] (2) Electrochemical analysis
[0188] The performance of the composite catalysts prepared in the above examples and comparative examples for electrochemical catalytic reduction of CO2 was tested below.
[0189] 100 mg of the catalyst was ultrasonically dispersed in a mixed solution of isopropanol (900 μl) and nafion (100 μl). The prepared slurry was sprayed on carbon paper (working area 2×2 cm 2 ) and dried at room temperature. Electrochemical tests were performed at room temperature using a CHI 660e electrochemical analyzer in an electrochemical reaction device separated by a proton transport layer (nafion-117). A three-electrode working system was used, with a platinum mesh electrode as the anode, an Ag / AgCl electrode in a saturated potassium chloride solution as the reference electrode, and a carbon paper prepared by spraying as the working electrode. All measured potentials were converted to reversible hydrogen electrode potentials using the following formula:
[0190] E(vs.RHE)=E(vs.Ag / AgCl)+0.059pH+0.197V
[0191] Electrochemical reaction devices such as Figure 4 As shown. The electrochemical reaction device includes:
[0192] Anode assembly 100, anode assembly 100 comprises an anode guide plate 101 and an anode electrode 103, and the surface of anode guide plate 101 facing anode electrode 102 is provided with an anode channel 102 for guiding and supporting electrolyte flow. Anode guide plate 101 is provided with an anode liquid flow field inlet 141 for supplying electrolyte to anode channel 102, and a liquid flow field outlet 142 for discharging electrolyte from anode channel.
[0193] The cathode assembly 200, from the cathode assembly 200 to the anode assembly 100, includes a cathode guide plate 202, a cathode diffusion layer 201, a catalyst layer 204 and a cathode electrolyte flow layer 206. The surface of the cathode guide plate 202 facing the cathode diffusion layer is provided with a cathode channel 203 for distributing the to-be-reduced substances. The cathode guide plate 202 is provided with a cathode gas inlet 251 and a cathode gas outlet 252.
[0194] The proton transport layer 300 is disposed between the cathode assembly 100 and the anode assembly 200. + ) along the direction of the arrow from the anode assembly 100 side through the proton transport layer 300 into the cathode assembly 200 side;
[0195] The power supply 400 is configured to apply a voltage between the anode assembly 100 and the cathode assembly 200 .
[0196] The working procedure of the electrochemical reaction device includes: introducing CO2 into the cathode gas inlet 251 of the electrochemical reaction device at a flow rate of 30 ml / min, and collecting the product from the cathode gas outlet 252. The supporting electrolyte (2M potassium hydroxide aqueous solution) is introduced from the cathode electrolyte flow layer 206 and the anode liquid flow field inlet 141 at a flow rate of 15 ml / min. A voltage of -1.1 V (vs RHE) is applied to the cathode of the above electrochemical reaction device, and it is operated for 30 minutes.
[0197] The gas product produced by the cathode enters the gas sampling loop of the gas chromatograph, and the gas phase components are analyzed by the gas chromatograph every 15 minutes. The Faraday efficiency of the gas product is calculated by the formula:
[0198]
[0199] Where ν (vol%) represents the volume of the corresponding gas component in the product, V (ml / min) is the gas flow rate, and I total (C / s) is the current value of the device in a stable state. The analysis results are shown in the following table:
[0200] Table 3
[0201]
[0202]
[0203] Analyzing the experimental data in Table 3, we can see that:
[0204] In Examples 1-5, the mass ratio of fullerene to copper element is 5-35:20, and C2H4 obtained by electrochemical catalytic reduction of CO2 has a Faraday efficiency of more than 30.03%.
[0205] In Examples 1, 2, and 5, the mass ratio of fullerene to copper element is 7-20:20, and C2H4 obtained by electrochemical catalytic reduction of CO2 has a Faraday efficiency of more than 42.85%.
[0206] In Example 1, the mass ratio of fullerene to copper element is 10:20, and C2H4 obtained by electrochemical catalytic reduction of CO2 has a Faradaic efficiency of 65.58%.
[0207] In Comparative Example 1, C 60 The content of is zero, and the C2H4 obtained by chemical catalytic reduction of CO2 has a Faradaic efficiency of only 24.12%.
[0208] In Comparative Example 2, the mass ratio of fullerene to copper element is 40:20, and C2H4 obtained by chemical catalytic reduction of CO2 has a Faraday efficiency of only 18.91%.
[0209] In Comparative Example 1, C 60 With a mass ratio of 3:20 to copper element, C2H4 obtained by chemical catalytic reduction of CO2 has a Faradaic efficiency of only 3.29%.
[0210] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A composite catalyst comprising: Copper-based micro-nanostructures; and Fullerene, wherein the fullerene is fixed on a copper-based micro-nanostructure; The mass ratio of fullerene to copper is 5-35:20; the copper-based micro-nanostructure includes Cu + and Cu 0 The Cu element Auger electron spectrum of the composite catalyst corresponds to Cu + and Cu 0 The peak area ratio of the characteristic peaks is 70-99:1-30.
2. The composite catalyst according to claim 1, wherein The mass ratio of fullerene to copper element is 5-30:
20.
3. The composite catalyst according to claim 1, wherein The mass ratio of fullerene to copper element is 7-20:
20.
4. The composite catalyst according to claim 1, wherein The mass ratio of fullerene to copper element is 8-14:
20.
5. The composite catalyst according to claim 1, wherein The mass ratio of fullerene to copper element is 9-12:
20. 6 . The composite catalyst according to claim 1 , wherein the copper-based micro-nano structure comprises one or more of the following: a copper-based micron structure and a copper-based nanostructure.
7. The composite catalyst according to claim 1, wherein the Cu element Auger electron spectrum of the composite catalyst corresponds to Cu + and Cu 0 The peak area ratio of the characteristic peaks is 70-95:5-30.
8. The composite catalyst according to claim 1, further comprising a carrier, wherein the copper-based micro-nano structure is fixed on the carrier.
9. The composite catalyst according to claim 8, wherein the carrier comprises micron-sized particles and / or nano-sized particles.
10. The composite catalyst according to claim 1, wherein the copper-based micro-nano structure has a 2 / g or more surface area.
11. The composite catalyst according to any one of claims 1 to 10, wherein the fullerene comprises C 2n 、M@C 2n 、M2@C 2n 、MA@C 2n 、M3N@C 2n 、M2C2@C 2n 、M2S@C 2n 、M2O@C 2n 、M x A 3-x @C 2n , C 2n H 2y , C 2n Cl 2y One or more of the following; The M and A are each independently one of Sc, Y and a lanthanide metal, and M and A are different; 25≤n≤60; 0≤x≤3; 0≤y≤20.
12. The composite catalyst according to claim 11, wherein 30≤n≤50。 13. The composite catalyst according to claim 11, wherein 1≤x≤2。 14. The composite catalyst according to claim 11, wherein 5≤y≤10。 15. The composite catalyst according to any one of claims 1 to 10, wherein the fullerene comprises one or more of the following: 60 , C 70 , C 76 , C 84 、Gd@C 82 , C 50 Cl 10 , C 60 Cl 10 Sc2C2@C 80 Sc3N@C 82 Sc2S@C 82 Sc2O@C 82 , C 60 H 10 , C 64 H4.
16. Use of the composite catalyst according to any one of claims 1 to 15 for electrochemical catalytic reduction of CO2 to obtain C2H4.
17. The use according to claim 16, wherein The Faradaic efficiency of obtaining C2H4 is above 30%.
18. A method for electrochemical catalytic reduction of CO2 to obtain C2H4, comprising: Bringing CO2 into contact with an electrode containing a catalyst; The catalyst is the composite catalyst according to any one of claims 1 to 15.
19. The method according to claim 18, wherein: The Faradaic efficiency of obtaining C2H4 is above 30%.
20. The method according to claim 18, further comprising the steps of: A voltage of -0.8 V vs. RHE to -1.3 V vs. RHE was applied to the electrodes.
21. An electrochemical reaction device comprising An electrode containing a catalyst, wherein the catalyst is the composite catalyst according to any one of claims 1 to 15; and a distributor configured to distribute CO2 to an electrode containing a catalyst; Optionally, the electrochemical reaction device is used for electrochemical catalytic reduction of CO2 to obtain C2H4.
22. A method for preparing a composite catalyst according to any one of claims 1 to 15, comprising the following steps: Providing a precursor, wherein the precursor contains a fullerene-copper co-precipitation product and / or a fullerene-copper co-milling product; calcining the precursor to obtain a calcined product; The calcined product is electrochemically reduced at a potential of -0.8 V vs RHE to -1.3 V vs RHE to obtain the composite catalyst; wherein the electrolyte for the electrochemical reduction is selected from one or more of sodium chloride solution, potassium chloride solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium hydroxide solution, potassium hydroxide solution and tetrabutylammonium hexafluorophosphonate solution.
Citation Information
Patent Citations
Fullerene-stabilized cuprous functional material as well as preparation method and application thereof
CN113842916A
Catalyst for preparing ethylene by reducing carbon dioxide, catalytic electrode and preparation method
CN114318406A